OPEN RESOURCES AS A SOLUTION FOR EDUCATIONAL CONTENT - Sabirovna , Yunusova Minavvarhon (International Journal of Business, Law and Political Science, 2024)
In the digital age, the accessibility and quality of educational content are critical factors influencing learning outcomes and educational equity. Despite the proliferation of educational resources, significant disparities remain in access to high-quality, up-to-date, and culturally relevant materials. Limited research has systematically evaluated the impact of open educational resources (OER) on bridging these gaps and enhancing learning experiences across diverse educational contexts. This study aims to assess the effectiveness of OER in addressing educational inequities by examining their influence on content accessibility, engagement, and academic performance. The analysis reveals that OER significantly improve access to high-quality educational materials, increase learner engagement, and enhance academic outcomes compared to traditional resources.This research uniquely contributes to the literature by providing empirical evidence on the broad efficacy of OER across various educational levels and disciplines, highlighting their potential as a transformative tool for achieving educational equity. The findings suggest that the adoption and integration of OER can serve as a viable strategy for educational institutions aiming to democratize access to knowledge and reduce disparities in learning opportunities, ultimately supporting more equitable educational environments.